2021
DOI: 10.16984/saufenbilder.853961
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cheese Whey for Production of Azurin by Pseudomonas aeruginosa

Abstract: Azurin which has attracted much attention as potential anticancer agent in recent years is a bacterial secondary metabolite. This copper-containing redox protein secreted by Pseudomonas aeruginosa has capability of preferentially entering into many human cancer cells and inducing apoptosis. In this study, whey which is the considerable by-product of the casein or cheese manufacture was used as azurin production medium by P. aeruginosa. Also, effects of copper (II) sulphate (CuSO4) and potassium nitrate (KNO3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…According to Lucakova et al (2022), wastewater obtained after the demineralisation of CW is the best substrate for the growth of spirulina (Limnospira maxima). In some studies, it has been reported that CW can be utilised to produce azurin, an anticancer agent, with the help of Pseudomonas aeruginosa ( € Unver, 2021). According to Tatoulis et al (2018), CW or winery effluents were co-treated using biological trickling filters under varied operating settings with hexavalent chromium.…”
Section: Potential Applications Of Cw For Various Product Formulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Lucakova et al (2022), wastewater obtained after the demineralisation of CW is the best substrate for the growth of spirulina (Limnospira maxima). In some studies, it has been reported that CW can be utilised to produce azurin, an anticancer agent, with the help of Pseudomonas aeruginosa ( € Unver, 2021). According to Tatoulis et al (2018), CW or winery effluents were co-treated using biological trickling filters under varied operating settings with hexavalent chromium.…”
Section: Potential Applications Of Cw For Various Product Formulationsmentioning
confidence: 99%
“…(2022), wastewater obtained after the demineralisation of CW is the best substrate for the growth of spirulina ( Limnospira maxima ). In some studies, it has been reported that CW can be utilised to produce azurin, an anticancer agent, with the help of Pseudomonas aeruginosa (Ünver, 2021). According to Tatoulis et al .…”
Section: Potential Applications Of Cw For Various Product Formulationsmentioning
confidence: 99%
See 2 more Smart Citations